Tracking the driving forces for the unfolding and folding of kidney bean protein isolates: Revealing mechanisms of dynamic changes in structure and function. (15th February 2023) - Yan, Xinyue; Jia, Yijia; Man, Hui; Sun, Shiyan; Huang, Yuyang; Qi, Baokun; Li, Yang
Graphical abstract: Highlights: The pH-shifting is irreversible, causes KPI depolymerization and rearrangement. Alkaline-shifting disrupts hydrogen bonds and electrostatic interactions of KPI. Acidic-shifting disrupts intermolecular hydrophobic interactions of KPI. Both acidic- and alkaline-shifting improve structures and functionalities of KPI. Abstract: Tracking the dynamic changes in the structure of kidney bean protein isolate (KPI) during extreme pH-shifting can reveal the different mechanisms that drive the unfolding and refolding of the protein from a conformational perspective and elucidate the relationship between its structure and function. The secondary and tertiary structures of KPI were analyzed using multispectral techniques. The results showed that acidic-shifting affected the hydrophobic interactions of KPI molecules, whereas alkaline-shifting affected hydrogen bonding and electrostatic interactions of the molecules. Therefore, alkaline-shifting was more likely to affect KPI conformation. SEM revealed that pH-shifting transformed the sheet structure of KPI into spheres and rods; moreover, it improved the surface hydrophobicity, thermal stability, emulsification, foaming, and antioxidant properties of KPI. In summary, each pH-shifting stage disrupts a different intermolecular force, resulting in protein conformational diversity, while structural changes further affect function. Therefore, pH-shifting treatment broadens the applications scope of KPI in the food industry.